The Extended-OPQ Method for User-Centered Quality of Experience Evaluation: A Study for Mobile 3D Video Broadcasting over DVB-H. (13th February 2011) - Strohmeier, Dominik; Jumisko-Pyykkö, Satu; Kunze, Kristina; Bici, Mehmet Oguz
Abstract : The Open Profiling of Quality (OPQ) is a mixed methods approach combining a conventional quantitative psychoperceptual evaluation and qualitative descriptive quality evaluation based on naïve participants' individual vocabulary. The method targets evaluation of heterogeneous and multimodal stimulus material. The current OPQ data collection procedure provides a rich pool of data, but full benefit of it has neither been taken in the analysis to build up completeness in understanding the phenomenon under the study nor has the procedure in the analysis been probed with alternative methods. The goal of this paper is to extend the original OPQ method with advanced research methods that have become popular in related research and the component model to be able to generalize individual attributes into a terminology of Quality of Experience. We conduct an extensive subjective quality evaluation study for 3D video on mobile device with heterogeneous stimuli. We vary factors on content, media (coding, concealments, and slice modes), and transmission levels (channel loss rate). The results showed that advanced procedures in the analysis cannot only complement each other but also draw deeper understanding on Quality of Experience.